Impulsive consumers and optimal social security - Findley, Thomas Scott, author; Kling, Robert W., advisor (Colorado State University. Libraries, 2007)
Unfunded social security programs are primarily justified on grounds that individuals have specific behavioral tendencies that lead to inadequate saving for retirement. To date, very little has been pursued in the way of theory to analyze this justification. I design a new model of consumer behavior that is consistent with many of the salient features of evidence on impulsive consumption behavior. In my model, "impulsive consumers" optimally formulate long-term plans, but often deviate from these consumption programs upon experiencing a psychological impulse to uncontrollably consume above and beyond. In order to examine how impulsive consumers fare in an unfunded social security program, I calibrate my model to match specific empirical features of aggregate life-cycle consumption. After calibrating the model, I employ dynamic welfare measures and find: (i) a significant welfare cost to consuming impulsively; (ii) a social security program (calibrated to the current U.S. program) does not generally improve the welfare of impulsive consumers; (iii) social security almost never improves the welfare of impulsive consumers under future demographics; and, (iv) the optimal social security tax rate is drastically smaller than the current U.S. rate.
Keywords: bounded rationality; dynamic optimization; impulsive consumers; life-cycle consumption; social security; models; studies; behavior; self control; demographics; calibration; boundary conditions; age; hypotheses; participation; planning; copyright; mouth; fingers and toes